Characterisation of a truncated Toxoplasma gondii surface antigen 2 (SAG2) secreted by the methylotrophic yeast Pichia pastoris. - Lau, Y.L.; Shamilah, H.; Fong, M.Y. (2006)
A truncated form of surface antigen 2 (SAG2) of the protozoan parasite Toxoplasma gondii was cloned and expressed in the methylotrophic yeast Pichia pastoris. This recombinant antigen, designated as recSAG2-N, contained only the N-terminal half of the native SAG2. The recSAG2-N was secreted by the Pichia pastoris into the culture supernatant, and it was harvested by using the trichloroacetic acid precipitation method. Specificity of recSAG2-N was evaluated in western blot assays. Fifty human serum samples, including 32 from confirmed cases of toxoplasmosis, were tested. Results from the assays showed that recSAG2-N reacted with sera from the toxoplasmosis cases only. In vivo experiments showed that serum from mice which received recSAG2-N reacted with the native SAG2 of T. gondii.